Integrated assessment of mangrove sediments in the Camamu Bay (Bahia, Brazil) - Paixão, Joana F. (2011)
CamamuBay,anEnvironmentallyProtectedArea,maybeaffectedbythepressuresoftourismandoil explorationintheadjacentcontinentalplatform.Thecurrentqualityofthemangrovesedimentswas evaluatedbyporewaterbioassaysusingembryosof Crassostrearhizophorae and byananalysisofbenthic macrofaunaanditsrelationshipswithorganiccompounds,tracemetalsandbioavailability.Porewater toxicityvariedfromlowtomoderateinthemajorityofthesamples,andpolychaetesdominatedthe benthos.TheGrandeIslandsamplingstation(Station1)presentedmoresandysediments,differentiated macrobenthicassemblagesandthehighestmetalconcentrationsinrelationtootherstationsand guidelinevalues,anditwastheonlystationthatindicatedapossiblebioavailabilityofmetals.Theorigin of themetals(mainlybarium)ismostlikelyassociatedwiththebariteoredepositslocatedintheGrande and Pequenaislands.Theseresultsmaybeusefulforfutureassessmentoftheimpactofoilexplorationin the coastalregion.